US Advanced Light Source set for $590m upgrade. (1st January 2023) - Gwynne, Peter
Abstract : A $590m upgrade to the Advanced Light Source will see the "brightness" of the facility increase by a factor of 100 and reduce the width of its X-rays beams from the current 100 μm to just a few microns.